Gaya Bahasa Mahasiswa STIEPAN: Pengaruh Media Sosial TikTok dan Instagram terhadap Penggunaan Bahasa Sehari-hari - Audria Balqis; Febrely Cahya Tsabitah; Zuen Shaqila; Nahira Ayuningtyas; Ni Nyoman Delanova Abjayoni Tantri; Anhar (Masyarakat Ekonomi Syariah Bogor, 2025)
This study aims to determine the effect of using TikTok and Instagram on the language style of STIEPAN students in daily communication. Data were collected through a Google Form filled out by 54 student respondents and analyzed using SPSS software with several stages, namely validity test, correlation test, and linear regression test. The validity test results show that out of 14 questionnaire items, 11 items were declared valid with a correlation value above 0.3, thus feasible for further analysis. Furthermore, the correlation test results indicate that only Instagram usage has a significant relationship with language style (r = 0.299; p = 0.028), while TikTok usage is not significant (r = 0.235; p = 0.087). This finding is supported by the linear regression analysis which produces the equation Y = 37.124 + 2.278X1 + 3.560X2. Thus, it can be concluded that Instagram has a greater influence on students’ language style compared to TikTok, especially in the use of slang, abbreviations, and non-standard language outside formal contexts.